The pattern and progression of hearing loss in Marfan Syndrome: A study of children and young adults. (November 2020) - Hamberis, Alexandra O.; Mehta, Charmee H.; Valente, Thomas A.; Dornhoffer, James R.; Nguyen, Shaun A.; Meyer, Ted A.
Abstract: Objective: (s) : To describe the prevalence, type, severity, and progression of hearing loss (HL) in children and young adults with Marfan Syndrome (MFS), and to evaluate the influence of comorbidities on HL. Study design: Retrospective database analysis. Results: Of 70 patients with MFS, 52.8% (N = 37) had HL. Within the HL group, 75.7% (N = 28) had bilateral HL, while 24.3% (N = 9) had unilateral HL. 21.4% (N = 15) had moderate or more severe HL. The overall prevalence of CHL was 40.5% (N = 15), SNHL 13.5% (N = 5), and mixed HL 37.8% (N = 14). The mean initial age of HL was 8.4 years (range 0.8–24.0). HL was more prevalent in patients with MFS who also experienced chronic otitis media (ES 1.00, 95% CI, 0.32–1.68) and skull anomalies (ES 0.75, 95% CI, 0.07–1.44) as well as for patients with hypertension (ES 2.17, 95% CI, −1.29-5.64). Conclusions: Children and young adults with Marfan syndrome have a high likelihood of hearing loss, with high rates of CHL, chronic otitis media, and Eustachian tube dysfunction. SNHL is also prevalent in this syndrome; hypertension increased the likelihood of SNHL. Early audiologic screening is needed to ascertain type of HL and to efficiently direct patient care in this population.